The Influence of Organizational Culture on Teacher Innovation Capability and Tacit Knowledge: A CB-SEM AMOS Analysis - Agus Purwanto; Anwar Sulaiman (AGUSPATI Research Institute, 2023)
- This study aims to measure the influence of organizational culture on teacher innovation capability in Indonesia mediated by tacit knowledge. This research method is a quantitative survey. The data collection technique in this study used an online questionnaire technique which was designed using a Likert scale of 1 to 7 and distributed to 468teachers selected by the simple random sampling method. This data processing tool uses Structural Equation Modeling (SEM) using AMOS (Analysis of Moment Structure) version 26. Before conducting data analysis, the validity and reliability of the questionnaire used is tested first. To measure its validity, the score of each question item is used which is correlated with the total item score in one variable. After testing the validity and reliability, then performed data analysis. Analysis and interpretation of data is carried out to answer the problems that have been formulated and answer the hypotheses. In this study, data analysis used Structural Equation Modeling (SEM) with AMOS software. The results of this study are organizational culture has a positive and significant effect on teacher innovation capability, Organizational culture has a positive and significant effect on explicit knowledge sharing. explicit knowledge sharing has positive and significant effect on teacher innovation capability.